Body Image Concerns as a Mediator between Instagram Use and Self-Esteem in Female Adolescents - Conti, Marco; Kovács, Eszter (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to investigate whether body image concerns mediate the relationship between Instagram use and self-esteem among female adolescents in Hungary. Methods and Materials: A descriptive correlational research design was employed with a sample of 400 female adolescents aged 14–18 years, selected based on Krejcie and Morgan’s sample size table. Participants completed three standardized instruments: the Instagram Addiction Scale, the Body Image Concern Inventory, and the Rosenberg Self-Esteem Scale. Data were analyzed using SPSS-27 for descriptive statistics and Pearson correlations, and AMOS-21 for structural equation modeling (SEM). Model fit was assessed using χ², χ²/df, GFI, AGFI, CFI, TLI, and RMSEA indices. Findings: Pearson correlation analysis revealed a significant positive relationship between Instagram use and body image concerns (r = .52, p < .001), a strong negative relationship between body image concerns and self-esteem (r = –.58, p < .001), and a moderate negative correlation between Instagram use and self-esteem (r = –.41, p < .001). SEM results demonstrated a good model fit (χ² = 118.34, df = 58, χ²/df = 2.04, CFI = 0.96, TLI = 0.95, RMSEA = 0.051). Path analysis indicated that Instagram use significantly predicted body image concerns (β = .52, p < .001) and that body image concerns negatively predicted self-esteem (β = –.49, p < .001). The direct path from Instagram use to self-esteem was significant (β = –.19, p = .001), while the indirect path via body image concerns (β = –.25, p < .001) was stronger, confirming partial mediation. Conclusion: Findings highlight that Instagram use exerts both direct and indirect negative effects on adolescent self-esteem, with body image concerns functioning as the primary mediating mechanism. These results underscore the importance of addressing body image perceptions in interventions aimed at mitigating the harmful psychological consequences of social media engagement among adolescent girls.